(untitled) (Research, Society and Development, 2021)
Practical activities are important resources for science teaching, however, the scarcity of biological materials prevents their widespread use in Basic Education. In this context, this study aims to analyze the contribution of the production of a zoological collection to the process of teaching and learning about arthropods in a class with 16 students from the 7th year of a public school in the interior of Rio Grande do Sul. It is a laboratory research established through an initial theoretical-practical approach to the content of arthropods, with subsequent collective production of a zoological collection of arthropods (covering collection, assembly and conservation processes). The analysis of the results occurred through observation and recording in a field diary. We obtained 16 specimens of the subphylum Chelicerata, seven specimens of Myriapoda, two specimens of Crustacea and 38 specimens of Hexapoda. The collection proved to be an efficient material for the teaching process on arthropods, since such a tool is low cost and has the potential to attract students’ interest and curiosity. In addition, it brings students closer to the content developed in the classroom, helping to understand morphological, anatomical, physiological and ecological aspects. In addition, it is concluded that it allowed to signal differences and clarify myths, contributing to a meaningful learning and to be used in future classes.